Visual Literacy of Traditional Play (Dentou Tekina Asobi) To Stimulate Cross-Cultural Understanding in The Dokkai Course - Widiati, Sri Wahyu; 'Izzati, Nur (KIRYOKU, 2026)
This study aims to explain how visual literacy using digital photos supports students’ reading comprehension and cross-cultural understanding in a dokkai (reading) course. Visual literacy in this study was implemented through digital photos and texts with a focus on traditional Japanese and Indonesian games, which provided a meaningful cultural context for comparison. Digital photos were obtained from online sources and were used to help students observe traditional play (dentoteki na asobi) and connect vocabulary, textual meaning, and cultural elements. Visual literacy provided initial support for reading, stimulated prediction and interpretation, and encouraged critical thinking about cross-cultural phenomena. This research employed a qualitative descriptive method to examine how digital photos were used as a dokkai learning medium and how visual literacy supported students’ exploration of cross-cultural understanding. The results showed that students were able to identify similarities and differences between traditional Japanese and Indonesian games, appreciated the cultural value of traditional play, and developed critical awareness of shifts between traditional and modern play culture.